The Implementation of Digital Storytelling Applications to Improve Elementary Students’ English-Speaking Skills - Lailatul Kodriyah; Radityo Tri Nugroho; Yudha Aprizani (Lembaga Pengembangan Kinerja Dosen, 2025)
English-speaking ability is a crucial communication skill that needs to be developed from an early age to enhance students’ competence in the globalized era. However, many elementary school students still struggle to speak English fluently due to the lack of interactive learning media and low self-confidence in expressing ideas. This study aims to analyze the implementation of a digital storytelling application as an innovative learning medium to improve students’ English-speaking skills. The research employed a Classroom Action Research (CAR) design integrating both qualitative and quantitative approaches. The study was carried out through four stages: planning, implementation, observation, and reflection. Data were collected through observations, interviews, and pre- and post-speaking tests to measure students’ improvement in fluency, pronunciation, vocabulary, and confidence. The findings indicate that the use of digital storytelling significantly enhanced students’ speaking performance, motivation, and engagement in learning activities. Furthermore, the interactive features of the application encouraged students to participate actively and creatively in storytelling sessions, creating a more enjoyable and meaningful language learning experience. Therefore, the integration of digital storytelling in English learning is recommended as an effective pedagogical strategy to foster communication competence and learner autonomy among elementary school students.